P 64 Effects of a combined physical and cognitive training on cognition and neurotrophic levels. Issue 10 (October 2017) - Woost, L.; Klein, T.A.; Roggenhofer, E.; Bazin, P.L.; Taubert, M.; Rjosk, V.; Garthe, A.; Kempermann, G.; Renner, U.; Stalla, G.; Obrig, H.; Villringer, A.
Abstract : Physical exercise is known to improve memory functions in both animals and humans by inducing various plastic changes in the hippocampus. The present study assumed that physical exercise thus could help to increase the effects of a subsequent hippocampus-dependent cognitive training on directly assessed training outcomes as well as on cognitive transfer measures covering spatial and verbal memory, spatial intelligence as well as attention measures. To identify possible mechanisms that support training-induced changes, we additionally examined brain-derived neurotrophic factor (BDNF), insulin-like growth factor I (IGF-I) as well as vascular endothelial growth factor (VEGF). We collected data from N = 99 young, healthy participants (60 females; age: 25.24 ± 3.55) who performed either eight twenty-minute sessions of a cycling exercise ( n = 26), 16 thirty-minute sessions of a computerized maze training ( n = 23), both training programs ( n = 24) or rested as passive controls ( n = 26). To examine both immediate and delayed training effects, we implemented four separate measurement occasions. Data analyses revealed that both the cycling exercise and maze training were highly effective as participants significantly improved their training outcomes from pre- to post-intervention, respectively. Moreover, participants in the combined condition demonstrated greater learning success in the first eight sessions of the maze training as compared to maze-training-only participants. This group difference, however, did not reach significance when considering all 16 maze training sessions simultaneously. At the level of cognitive transfer, we observed a significantly positive effect of our maze training on verbal memory retention as compared to passive controls. In contrast, neither the cycling exercise nor the combined condition led to significant changes in cognitive transfer. The assessed neurotrophic levels widely remained unaffected by our trainings. Post-maze IGF-I, however, was significantly reduced in the combined condition as compared to maze-training-only participants. Correlation analyses further revealed a significantly positive association between pre- to post-cycling changes in VEGF on the one hand and pre- to post-cycling changes in one of the attention measures on the other hand. The present study yields preliminary evidence for a direct catalytic effect of physical exercise on subsequent hippocampus-dependent learning in a young, healthy sample. This effect, however, did not transfer to non-trained cognitive abilities. Negative findings on both cognitive transfer and neurotrophic changes are discussed in light of methodological limitations of the study and are linked to the current literature.